2004
DOI: 10.1016/j.bbmt.2003.11.005
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of tacrolimus and mycophenolate mofetil graft-versus-host disease prophylaxis in childhood and adolescent allogeneic stem cell transplant recipients

Abstract: Tacrolimus (FK506)/mycophenolate mofetil (MMF) has been demonstrated to be an effective salvage therapy for steroid-resistant chronic graft-versus-host disease (GVHD), but its effectiveness as prophylaxis for acute GVHD (aGVHD) is unknown. We investigated the safety and efficacy of FK506/MMF in preventing aGVHD and sparing the use of methotrexate and methylprednisolone in childhood and adolescent allogeneic stem cell transplant (AlloSCT) recipients. Thirty-four childhood and adolescent patients (median age, 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
90
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 34 publications
0
90
1
2
Order By: Relevance
“…Both groups concluded that the combination was effective and safe. 29,30 Retrospective comparisons revealed that the rate of acute GVHD was at least comparable to standard CYA/MTX.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups concluded that the combination was effective and safe. 29,30 Retrospective comparisons revealed that the rate of acute GVHD was at least comparable to standard CYA/MTX.…”
Section: Discussionmentioning
confidence: 99%
“…infusion or 0.12 mg/kg orally (PO) twice a day was started (dose adjusted to maintain blood levels of 10-20 ng/mL) on day − 8. 19 MMF was administered at 900 mg/m 2 q6-8 h PO or i.v. starting on day +1.…”
Section: Gvhd Prophylaxis and Gradingmentioning
confidence: 99%
“…19,20 MMF was tapered if patients had ⩽ grade II aGVHD on day +180 and tacrolimus was tapered upon conclusion of the MMF taper. 19,20 aGVHD and chronic GVHD (cGVHD) were graded according to Seattle consensus criteria. 21 Supportive care and infection prophylaxis Sargramostim (250 μg/m 2 /day) was started i.v.…”
Section: Gvhd Prophylaxis and Gradingmentioning
confidence: 99%
“…tacrolimus in combination with mycophenolate mofetil and 16% in those receiving CSP. 5,21 Only 1 (3%) of our patients developed PRES requiring discontinuation of tacrolimus. One additional patient developed tremors (mild neurotoxicity) associated with tacrolimus; however, this patient did not require discontinuation of the drug.…”
Section: Discussionmentioning
confidence: 74%
“…administration of tacrolimus. 7,21 Tacrolimus is a proven immunosuppressant effective in the prevention of aGVHD in children. The incidence of aGVHDXGrade II in this study (28%) is similar to the reported incidence of aGVHD in pediatric population using both related and unrelated donors with a variety of GVHD prophylaxis.…”
Section: Discussionmentioning
confidence: 99%